التغيرات الهيكلية في الأقتصاد العرقي دراسة قياسية للفترة 1975 – 1997 - الصفار, احمد سليمان (Sulaimani Journal for Humanities, 2001)
The purpose of this study is to estimate and evaluate the determinants of the structural changes in iraqi gross domes tic product assuming that the share of the agriculture product sector decline and that of industry and tertiary sectors increases with an increase in the real per capita income, it is found that the share of industrial production declined and that for agriculture and tertiary increased among the period 1981-1997, as a result of declining the real per capita income.